A Pilot Study of Interpersonal Psychotherapy for Alcohol-Dependent Women with Co-Occurring Major Depression. Issue 3 (July 2013) - Gamble, Stephanie A.; Talbot, Nancy L.; Cashman-Brown, Sarah M.; He, Hua; Poleshuck, Ellen L.; Connors, Gerard J.; Conner, Kenneth R.
Background: Co-occurring major depression is prevalent among alcohol-dependent women and is a risk factor for poor treatment outcomes. This uncontrolled pilot study tested the feasibility, acceptability, and initial effects of interpersonal psychotherapy (IPT) for women with co-occurring alcohol dependence and major depression (AD-MD) in an outpatient community addiction treatment program. Methods: Fourteen female patients with concurrent diagnoses of alcohol dependence and major depression participated. Assessments were conducted at baseline, midtreatment (8 and 16 weeks), posttreatment (24 weeks), and follow-up (32 weeks). Results: Participants attended a mode of 8 out of 8 possible sessions of IPT in addition to their routine addiction care, and reported high treatment satisfaction on the Client Satisfaction Questionnaire-8. Women's drinking behavior, depressive symptoms, and interpersonal functioning improved significantly over the treatment period and were sustained at follow-up. Conclusions: These preliminary findings suggest that IPT is a feasible, highly acceptable adjunctive behavioral intervention for AD-MD women.